Pola Asuhan Keperawatan Terhadap Pasien dengan Masalah Post Stroke - Muzakir Muhammad Amin (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Stroke is the presence of clinical signs that develop rapidly due to focal brain function disorders. Stroke occurs suddenly but has long-term effects such as disability, emotional problems, depression and also changes in social relationships. A stroke occurs when the blood supply to the brain stops suddenly, thereby blocking the supply of oxygen, which is a vital necessity for the brain, causing a decrease in normal brain function. Cases of stroke need to be handled by the patient's family quickly and precisely so that the patient gets help according to the condition of the stroke he is experiencing. Based on this, a study is needed related to nursing care for stroke patients. The method used in this study is a descriptive method with a case study approach that is carried out on the pattern of nursing care in stroke patients. From the research results obtained from patients, namely patients complaining of no appetite, difficulty lifting the left leg and difficulty speaking. There are 3 nursing problems that arise in patients, namely nutritional imbalances less than body requirements, impaired physical mobility and, impaired verbal communication. This is based on the results of interviews and observations found due to lack of knowledge of the patient's family on how to treat stroke patients.